HUBUNGAN PENGETAHUAN IBU AKSEPTOR KB TENTANG METODE KONTRASEPSI JANGKA PANJANG (MKJP) DENGAN KEIKUTSERTAAN MENJADI AKSEPTOR MKJP DI KELURAHAN NGAL KARIMUN TAHUN 2018 - Suzanty, Heny; Mariyana, Mariyana (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2019)
Long-Acting Reversible Contraceptives (LARCs) are the most effective method of birth control for long-term period of time. The IUD, Implant, MOW and MOP are some of the LARCs example. Thi study aims to investigate the correlation of knowledge levels of the female acceptors of Long-Acting Reversible Contraceptives (LARCs) and their participation in becoming LARCs’ acceptors with analytical survey using a cross sectional approach study design. The population of this study was 147 people and further through simple random sampling, 62 respondents were selected as the sample. The research was held from February to July 2018 at Kelurahan Ngal of Karimun. As the data collection instrument, questions were utilized, then the data was analyzed using Chi-Square statistical test. The result of the study concerning the age, education, number of children and type of contraception of the respondents, 38 people (61.3%) have poor knowledge about the LARCs, The active acceptors of LARCs family planning in Kelurahan Ngal is noted to be the lowest participation since only 13 respondents (0.01%), On the other hand, Chi-Square test at significant level of α = 0.05 obtains p value = 0.026 meaning that there is a significant correlation between female acceptors’ knowledge about LARCs and their involvement in becoming active acceptors of LARCs. The Communication, Information, and Education on family planning, whereas, the availability of costs and services and means of transportation were addressed as the problems. Finally, it is hoped for the health workers to be able to improve family planning counseling as well as qualify and trustworthy service to all people, particularly female contraceptive acceptors about the LARCs.